Gelatin Grafted Methyl Nadic Anhydride and Substitution With Salbutamol (Baghdad Science Journal, 2016)
Gelatin a promising biomaterial which is useful and interesting natural polymer which offer possibilities of chemical modification through grafted copolymerization with an saturated acid anhydride such as methyl nadic anhydride formatted gelatin –g- methyl nadic anhydride copolymer (A1), then modified to its corresponding polymer (A2) by substituted salbutamol as useful derivative as biomaterial .the prepared drug biopolymer was characterization by FTIR spectroscopy and thermal analysis was studied controlled drug release was measured in different buffer solution at 37C0 .